Thoughts from my one-evening Ramadan experience - Hasan, Md. Mahmudul (About Islam, 2019)
It seems that the majority of Muslims are far away from the correct teachings of Islam and have reduced their religion to a set of rituals and ceremonies that may smack of religiosity but are devoid of substance. This suggests that people who deliver speeches on Islam on a regular basis have a responsibility to touch on down-to-earth issues and offer the audience advice on the problems which occur at each stage of our everyday life. Unfortunately, many speakers on Islam repeat only issues of rituals, and that in an otherworldly fashion.